Implementasi Manajemen Pendidikan Di Pusat Kegiatan Belajar Masyarakat (PKBM) Langgeng Ikhlas Depok - Permana, Putut Said (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2023)
This research aims to understand how the functions of educational management are implemented at PKBM Langgeng Ikhlas Depok. The research employs a qualitative approach. Research data were collected through observation and interviews. Data analysis utilized the Miles and Huberman analysis model, encompassing data reduction, data presentation, and conclusion drawing. The research findings indicate that PKBM Langgeng Ikhlas Depok has effectively executed educational management functions, which include: (1) structured planning, designing educational programs based on clear analyses of needs and objectives; (2) effective organization within PKBM, evidenced by a well-coordinated organizational structure that facilitates task distribution and responsibilities; (3) implementation that bridges plans with tangible actions; (4) meticulous supervision that monitors plan execution and regularly assesses performance. The research also uncovers challenges faced in management, particularly relating to facilities and infrastructure, as well as the community's learning enthusiasm. These research outcomes are anticipated to serve as a reference for non-formal educational institutions facing similar conditions, seeking to enhance the quality of educational services.Keywords: PKBM; educational management; non-formal education